Fatty Acids Composition of Seed & Fleshoil of Prunus Microcarpa Fruit - Hussain, Faiq H.S.; Majid, Sirwa N. (Sulaimani Journal for Pure and Applied Sciences, 2003)
Prunus microcarpa fruit seed and flesh oils have been extracted and found to be 15.7671% and 0.3710 % respectively. The oils was analyzed qualitatively and quantitatively for the fatty acids content using GLC gas liquid chromatography. It showed that the seed oil contains five fatty acids: myristic, palmitic, stearic, oleic and, linoleic; while the flesh oil contains nine fatty acids: lauric, myristic, palmitic, palmitoleicl, stearic, oleic, linoleic, linolenic„ and erucic. Some of the identified fatty acids were found to be unsaturated. The result indicates that it can be used as potential source for oil which may be utilized for different purposes.
Keywords: GLC; fatty acids; prunus microcarpa